1994
DOI: 10.1056/nejm199405053301801
|View full text |Cite|
|
Sign up to set email alerts
|

Dose and Dose Intensity of Adjuvant Chemotherapy for Stage II, Node-Positive Breast Carcinoma

Abstract: The doses of chemotherapy used to treat breast cancer, especially early breast cancer, should not be reduced if the maximal benefit is to be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
221
2
6

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 624 publications
(232 citation statements)
references
References 13 publications
3
221
2
6
Order By: Relevance
“…7 Several studies and retrospective analyses suggest a sigDespite adjuvant chemotherapy the prognosis of patients with breast cancer and a high number of nificant dose-response relationship in metastatic and primary breast cancer. [8][9][10][11] Attempts to further improve these involved axillary lymph nodes is very poor. The aim of the present study was to evaluate the efficacy of highresults by increasing the dose of chemotherapy have met only limited success, mainly due to profound myelodose chemotherapy with autologous bone marrow support in patients with seven or more involved axillary suppression.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies and retrospective analyses suggest a sigDespite adjuvant chemotherapy the prognosis of patients with breast cancer and a high number of nificant dose-response relationship in metastatic and primary breast cancer. [8][9][10][11] Attempts to further improve these involved axillary lymph nodes is very poor. The aim of the present study was to evaluate the efficacy of highresults by increasing the dose of chemotherapy have met only limited success, mainly due to profound myelodose chemotherapy with autologous bone marrow support in patients with seven or more involved axillary suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few controlled prospective studies of the dose-response relationship in breast cancer have been published, and the results have not been consistent. A few studies have demonstrated a survival benefit from receiving a higher dose intensity (Carmo-Pereira et al, 1987;Tannock et al, 1988;Wood et al, 1994), while many controlled studies have failed to demonstrate any dose-response relationship (Hortobagyi et al, 1987a, b;Ludwig Breast Cancer Study Group, 1985;Walters et al, 1992;Fumoleau et al, 1993).…”
mentioning
confidence: 99%
“…Recently, Goldhirsch et al concluded that the many variations in CMF regimens did not improve results (Goldhirsch et al, 1998a(Goldhirsch et al, , 1998b. However, several studies have suggested that a higher dose or dose intensity of chemotherapy may improve disease-free and overall survival (Bonadonna and Valagussa, 1981;Hryniuk and Bush, 1984;Hryniuk and Levine, 1986;Hryniuk et al, 1987;Tannock et al, 1988;Ang et al, 1989;Engelsman et al, 1991;Wood et al, 1994). Bonadonna and Valagussa (1981) suggested after a retrospective analysis, that the effectiveness of adjuvant CMF depends on the total dose actually administered.…”
Section: Discussionmentioning
confidence: 99%
“…CMF was only useful when given ≥ 85% of the planned dose (Bonadonna and Valagussa, 1981). Wood et al reported the results of a prospective, randomized trial of adjuvant cyclophosphamide, doxorubicin and 5-fluorouracil in three dose levels (Wood et al, 1994). The women treated with a moderate or high dose intensity had a significantly longer disease-free and overall survival than those treated with a low dose intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation